2021
DOI: 10.1111/cts.13192
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic/pharmacodynamic modeling for dose selection for the first‐in‐human trial of the activated Factor XII inhibitor garadacimab (CSL312)

Abstract: Factor XII (FXII) is a serine protease involved in multiple cascades, including the kallikrein-kinin system. It may play a role in diseases in which the downstream cascades are dysregulated, such as hereditary angioedema. Garadacimab (CSL312) is a first-in-class, fully human, monoclonal antibody targeting activated FXII (FXIIa).We describe how translational pharmacokinetic (PK) and pharmacodynamic (PD) modeling enabled dose selection for the phase I, first-in-human trial of garadacimab.The PK/PD data used for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Findings from our study lead to an improved understanding of the MOA for garadacimab, validating its observed preclinical and clinical efficacy in the reduction of HAE attacks. 8 , 10 , 12 The studies also demonstrate that the solvent-accessibility approach, accomplished using HDX-MS complemented by SPR and EM, is a valuable tool to study protein binding in antigen/antibody complexes, particularly when the crystal structures are not immediately available. 16 …”
Section: Discussionmentioning
confidence: 91%
“…Findings from our study lead to an improved understanding of the MOA for garadacimab, validating its observed preclinical and clinical efficacy in the reduction of HAE attacks. 8 , 10 , 12 The studies also demonstrate that the solvent-accessibility approach, accomplished using HDX-MS complemented by SPR and EM, is a valuable tool to study protein binding in antigen/antibody complexes, particularly when the crystal structures are not immediately available. 16 …”
Section: Discussionmentioning
confidence: 91%
“…Richter et al showed in 2020 that mAbs SC absorption was generally faster in animals than in humans due to their physiology [ 12 , 50 , 66 ]. One of the translational methods for K a could be to scale the parameters from the monkey as the other parameters with an allometric exponent of −0.25 [ 29 , 67 ], even if the C max can be regularly over-predicted with this exponent and the translation is considered as unreliable by some papers [ 63 , 66 ]. In other papers, K a was assumed to be the same in humans and in monkeys [ 51 ].…”
Section: Mabs Pk Translationmentioning
confidence: 99%
“…To translate the linear parameters part, he used an allometric scaling [ 67 ]. This method is largely used and found in each paper with a mAbs TMDD [ 29 , 51 , 63 , 73 ].…”
Section: Mabs Pk Translationmentioning
confidence: 99%
See 2 more Smart Citations